How to Stimulate Single Mothers on Welfare to Find a Job; Evidence from a Natural Experiment - Marike Knoef; Jan C. van Ours (Center for Economic Studies and ifo Institute (CESifo), 2014)
We present the results from a natural experiment in which single mothers on welfare were stimulated to find a job. Two policy instruments were introduced: an earnings disregard and job creation. The experiment was performed at the level of municipalities in The Netherlands, a country with relatively high benefits and low incentives for single mothers to leave welfare for work. In our analysis, we make a distinction between native and immigrant welfare recipients. For immigrant single mothers and some groups of native single mothers we find a positive employment effect of an earnings disregard. Job creation in addition to the earnings disregard increased working hours for some groups of single mothers. Although the outflow from welfare was not affected, welfare expenditures were reduced.
Keywords: C41; C93; I38; J64; 330; welfare; single mothers; natural experiment